2023
DOI: 10.1097/md.0000000000033342
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of history of fractures and hypertension on the risk of all-cause death from osteoporosis: A retrospective cohort study

Abstract: To assess the coexistence effect between history of fractures and hypertension on the all-cause death risk of osteoporosis. In this retrospective cohort study, some characteristics of osteoporosis patients aged ≥ 20 years were extracted from the National Health and Nutrition Examination Survey (NHANES) database (2005–2010, 2013–2014), such as age, gender, smoking, drinking, the history of diabetes, cardiovascular and cerebrovascular diseases, fractures and hypertension. The outcome of this study was defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“… Chen et al (2023) have shown that the greatly increased risk of hip fracture in hypertension patients exists in both short-term and long-term courses of hypertension. The results of this study displayed that there were statistical differences in blood pressure between the osteoporosis group and the non-osteoporosis group ( P < 0.05), and there was a correlation between hypertension and bone mineral density T-score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Chen et al (2023) have shown that the greatly increased risk of hip fracture in hypertension patients exists in both short-term and long-term courses of hypertension. The results of this study displayed that there were statistical differences in blood pressure between the osteoporosis group and the non-osteoporosis group ( P < 0.05), and there was a correlation between hypertension and bone mineral density T-score.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is a systemic and metabolic bone disease characterized by low bone mass, compromised bone microarchitecture, and increased bone fragility, ultimately leading to fractures and associated clinical manifestations, such as reduced bone mineral density, degraded bone microstructure, chronic pain, and diminished mobility ( Bover et al, 2018 ; Chen et al, 2023 ). With its highest incidence among middle-aged and elderly individuals, osteoporosis poses a significant burden on this population ( Peng et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%